Tourism Resilience Process During Pandemic with Big Data Insight - Paramartha, Dede Yoga; Deli, Nensi Fitria; Fitriyani, Ana Lailatul; Pramana, Setia (Jurnal Ikatan Sarjana Ekonomi Indonesia, 2021)
Tourism, which is one of the pillars of the Indonesian economy, has experienced a shock due to the COVID-19 pandemic. This study aims to identify tourism resilience and its relation to the Indonesian economy during the pandemic. Subsequent to this, this study also investigates the competitiveness of tourism in responding to government policies regarding the five national tourism priorities. Descriptive analysis of data sourced from big data is used to support the analysis of tourism resilience in terms of accommodation and accessibility. In addition, Principal Component Analysis is used to build the tourism competitiveness measure of the five priority tourism destinations. The results showed that big data proxy indicators related to tourism generally show recovery signals in the new normal period, even though it hasn’t returned to its pre-pandemic condition and slightly decreased in early 2021. The improvement in this sector was mostly driven by domestic tourist. In terms of the economy, the added value of tourism has decreased considerably during 2020. In addition, based on the measure of tourism competitiveness, Central Java and North Sumatra are provinces that have good support systems for priority tourist destinations in their respective regions.